2021
DOI: 10.1186/s12879-021-06801-5
|View full text |Cite|
|
Sign up to set email alerts
|

Gender differences among patients with drug resistant tuberculosis and HIV co-infection in Uganda: a countrywide retrospective cohort study

Abstract: Background Gender differences among patients with drug resistant tuberculosis (DRTB) and HIV co-infection could affect treatment outcomes. We compared characteristics and treatment outcomes of DRTB/HIV co-infected men and women in Uganda. Methods We conducted a retrospective chart review of patients with DRTB from 16 treatment sites in Uganda. Eligible patients were aged ≥ 18 years, had confirmed DRTB, HIV co-infection and a treatment outcome regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
4
13
0
Order By: Relevance
“…Interestingly, in our study, gender, was found not to be a statistically significant factor affecting the survival of TB patients. This result is consistent with the studies that were conducted in Uganda and Brazil (32,33) but contradicts the findings of other studies that were conducted in Finland, Brazil and Singapore (34-36) that have found male TB patients to be at higher risk of dying due to TB. The differences noted could be attributed to a number of reasons including use of fixed effect models without accounting for catchment area heterogeneity and arbitrary choice of distribution for the hazard function.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, in our study, gender, was found not to be a statistically significant factor affecting the survival of TB patients. This result is consistent with the studies that were conducted in Uganda and Brazil (32,33) but contradicts the findings of other studies that were conducted in Finland, Brazil and Singapore (34-36) that have found male TB patients to be at higher risk of dying due to TB. The differences noted could be attributed to a number of reasons including use of fixed effect models without accounting for catchment area heterogeneity and arbitrary choice of distribution for the hazard function.…”
Section: Discussionsupporting
confidence: 85%
“… 29 We suggest that this finding is potentially explained by the notion that men are more likely to consume more tobacco and alcohol than women. 30 Moreover, another reason may be that men are less compliant with TB treatment than women, thus increasing their risk of developing MDR-TB. 31 In our study, it was found that patients aged 45 years and older with suspected TB were more likely to develop MDR-TB than patients aged less than 45 years.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar retrospective study of 666 drug-resistant TB/HIV-1 coinfected patients in Uganda, 60.2% were men, with a median age of 37 years. In addition, mortality following treatment failure was higher in men (25.7%) than in women (18.5%, P = 0.04) [16]. Table 1 provides a summary of studies that have addressed the male sex bias in TB/HIV-1 coinfection.…”
Section: Sexmentioning
confidence: 99%